Organising the recovery process within the annual training cycle for elite basketball players - Andreev, D.S.; Konovalov, I.E.; Parfenova, L.A.; Andreev, V.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to conduct an experimental evaluation of a model for organising the recovery process for student basketball players with competitive experience within a one-year training cycle. Methods and structure of the study. The following methods were employed in this research: analysis and synthesis of scientific and methodological literature, questionnaires, factor analysis, pedagogical experiments, modelling, testing, and methods of mathematical statistics. The study was conducted at the Volga State University of Physical Culture, Sport and Tourism, Kazan (experimental group) and the Orel State University named after I.S. Turgenev, Orel (control group). 30 qualified basketball players, members of university national teams, took part in the experiment, divided into two groups of 15 people each. Results and conclusions. In the experimental group, a specially developed model for organising the recovery process was applied, whilst the athletes in the control group carried out recovery activities independently, following their coach’s recommendations. The effectiveness of the model for organising the recovery process was tested as part of a pedagogical experiment by examining changes in the indicators of physical, technical, functional and psychological fitness among qualified basketball players: Physical fitness: in the experimental group, improvements in general and specific physical fitness indicators were recorded in the following ranges: 2.29–23.06% and 4.12–10.70%, respectively. Technical fitness: in the experimental group, improvements in technical fitness indicators were recorded within the following range: 34.32–61.80%. Functional fitness: in the experimental group, improvements in functional fitness indicators were recorded within the following ranges: respiratory system (spirometry) 12.55–21.62%; overall fitness (Wingate test) 10.26–23.12%; heart rate response to exercise 6.98–9.66%; Romberg’s test (stability platform) 13.84–37.69%, respectively. Psychological fitness: in the experimental group, improvements in psychological fitness indicators were recorded within the range of 8.93–25.56%. Improvements in all indicators studied were less pronounced in the control group. The experimental model developed allows for the integration of recovery measures into the training process of elite basketball players, taking into account the loads they undergo (training and competitive), as well as the characteristics and specifics of the training periods within the annual cycle. The effectiveness of the model was verified by assessing changes in the indicators of physical, technical, functional and psychological fitness of skilled basketball players, where a more significant improvement in results was observed in the experimental group compared to the control group in virtually all indicators studied. Thus, based on the results of the study, it can be concluded that the model for organising the recovery process for skilled basketball players in university basketball teams has proven its effectiveness following its trial.